Agglomeration and growth with and without capital mobility - Richard Baldwin; Rikard Forslid; Philippe J. Martin; Gianmarco I. P. Ottaviano; Frédéric Robert-Nicoud (Hamburg Institute of International Economics (HWWA), 2001)
This paper presents a simple framework in which the location and the growth rate of economic activities are endogenous and interact. We show that the nature of the equilibrium and of the relation between growth and location depends fundamentally on whether capital is assumed to be mobile (in which case we interpret it as physical capital) or immobile (human capital). In the first case, with constant returns to scale, growth and location are independent and no divergence or convergence process takes place. We show that newly created firms can relocate to the poor region, even though there is always a higher share of firms in the rich region, if the industry is competitive and if the return to capital is low. With immobile capital, a process of convergence between regions takes place when transaction costs on goods are sufficiently high but a process of ,,catastrophic“ agglomeration occurs when these costs are sufficiently high and regional inequality is not affected between regions. With localized technological spillovers, higher spatial concentration of economic activities spurs growth, whether capital is mobile or not. This implies that lowering transaction costs on goods can spur growth but increase regional inequality. Lowering transaction costs on ,,trade in technologies“ between regions may increase both regional equality and growth.
Keywords: 330; Raumwirtschaftstheorie; Regionale Wachstumstheorie; Agglomerationseffekt; Standorttheorie; Spillover-Effekt; Internationale Kapitalmobilität; Kern-Peripherie-Beziehung; Theorie